Yes we (still) can politics in the age of Obama, Twitter and Trump - Pfeiffer, Dan. (London Biteback Publishing, 2018)
On November 9th, 2016, Dan Pfeiffer woke up like most of the world wondering WTF just happened. How had Donald Trump won the White House? How was it that a decent and thoughtful president had been succeeded by a buffoonish reality star, and what do we do now?
Keywords: Obama, Barack